Analysis of Environmentally Friendly Buildings at Tartilul Qur'an Al-Munawwaroh Gresik Boarding School to Support Eco-Pesantren (Journal Intellectual Sufism Research (JISR), 2022)
Abstract.This study aims to analyze the Tartilul Qur'an Al-Munawwaroh Gresik Islamic Boarding School building in order to realize the eco-Islamic boarding school program. This type of research is a qualitative research that is descriptive and analytical in nature. The results of the study show that the impact of the post-truth phenomenon which is currently rife can be minimized by educating social network users about self-control in the use of social media and being more critical in following the trend that is currently booming but whose validity is unclear. Thus it can be concluded that digital literacy can be used as a solution in the post-truth phenomenon in the era of information disclosure.